Guilds, Guild Unions, Guild Courts in Transylvanian Saxon Towns in the Sixteenth Century - Derzsi, Julia (Historical Studies on Central Europe, 2024)
Under the auspices of the Universitas, the common self-governing body of the Transylvanian Saxon towns and seats, the guilds’ statutes were revised between 1539 and 1582: obsolete rules were abolished, and new ones were introduced where they had not existed before. According to the literature, this process marked a turning point in the relationship between the municipal authorities and the guilds, insofar as the town councils intervened in the guilds’ internal affairs, particularly in their powers to judge misconduct and disciplinary offences. But even before the new regulations, the guilds’ powers were limited to settling disputes between members at a lower instance, and even when they formed unions for common defence or drew up common statutes, they enjoyed no greater autonomy. The paper provides an overview of the activities of the guild courts, with case studies. It seeks to show the powers the guilds had in disciplinary matters and how these changed with the growing power of local government and the use of public authority. It argues that the authorities’ intervention in the guilds’ powers was not so much a restriction as a clarification of their entitlements, while ensuring that arising cases were appropriately dealt with, and that normative regulation played an important role in this process, defining the various facts and circumstances and transferring offences such as bodily harm, counterfeiting, and fraud to ordinary courts. At the same time, the guilds retained their power to deal with minor disputes between craftsmen, insults, and moral offences; under the pressure of the Reformation and the spread of Protestant morality, their disciplinary powers were greatly extended.